2019
DOI: 10.18502/kss.v3i13.4206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Liquidity, Firm Size, and Profitability on the Firm Value with Mediating Leverage

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
71
0
38

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 4 publications
25
71
0
38
Order By: Relevance
“…The relationship between profitability, capital structure, and firm value has been empirically studied by Chen & Chen (2011) and the results showed profitability affects firm value directly and indirectly through the use of capital structure as a mediator. The same result was also reported by (Hermuningsih, 2012;Thaib & Dewantoro, 2017;Zuhroh, 2019).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The relationship between profitability, capital structure, and firm value has been empirically studied by Chen & Chen (2011) and the results showed profitability affects firm value directly and indirectly through the use of capital structure as a mediator. The same result was also reported by (Hermuningsih, 2012;Thaib & Dewantoro, 2017;Zuhroh, 2019).…”
Section: Introductionsupporting
confidence: 88%
“…Several empirical studies on the relationship between capital structure and firm value have reported different results, for example, Chen & Chen (2011) found leverage to generally have a very negative effect on firm value and the same finding was reported by (Ambarwati & Stephanus, 2014;Dutta et al, 2018;Ernawati & Widyawati, 2015;Rayan, 2008;Sujoko & Soebiantoro, 2007;Zuhroh, 2019). In other studies, leverage was reported to have a significant positive impact on firm value (Anton, 2016;Cheng & Tzeng, 2011;Putri & Ukhriyawati, 2016).…”
Section: Introductionmentioning
confidence: 84%
“…Hasil tpenelitian tterdahulu tyang tdilakukan toleh tPratama & Wiksuana (2016), Mukherjee & Sen (2018) Suatu tperusahaan tharuslah tberada tdalam keadaan yang menguntungkan (profitable), tkarena ttanpa tadanya tkeuntungan takan tsulit tbagi tperusahaan untuk tmenarik tmodal tdari tluar tperusahaan tatau tinvestor (Zuhroh, 2019). Perusahaan tyang tmemiliki ttingkat tprofitabilitas tyang ttinggi takan tdiminati sahamnya toleh tinvestor, tsehingga tprofitabilitas tdapat tmempengaruhi tnilai perusahaan.…”
Section: Gambar 1 Grafik Indeks Harga Saham Perusahaan Real Esate Daunclassified
“…Investor yang mengevaluasi bahwa suatu perusahaan memiliki prospek yang baik di masa depan cenderung membeli saham perusahaan. Akibatnya, permintaan tinggi untuk saham menyebabkan harga saham menjadi lebih tinggi karena investor memberikan nilai tinggi kepada perusahaan (Zuhroh, 2019)).…”
Section: Pendahuluanunclassified